2008
DOI: 10.2139/ssrn.1157769
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Dynamics in a Target Zone - A Heterogeneous Expectations Approach

Abstract: The target zone model of Krugman (1991) has failed empirically. In this paper, we develop a model of the exchange rate with heterogeneous agents in a free floating and a target zone regime. We show that this simple model mimics the empirical puzzles of exchange rates: excessive volatility, fat tails, volatility clustering, and disconnection from the fundamentals. In addition, the target zone regime replicates a reduced nominal volatility for the same level of fundamental volatility as in the free floating regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 108 publications
2
15
0
Order By: Relevance
“…We provide clear support for the core assumptions of chartist-fundamentalist models, such as formulated by De Grauwe and Grimaldi (2006), Bauer, De Grauwe, andReitz (2009) or Dieci and. In particular, we find that (1) chartists and fundamentalists do indeed form different exchange rate expectations; chartists' expectations are more in line with trends while fundamentalists consider mean reversion slightly more.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We provide clear support for the core assumptions of chartist-fundamentalist models, such as formulated by De Grauwe and Grimaldi (2006), Bauer, De Grauwe, andReitz (2009) or Dieci and. In particular, we find that (1) chartists and fundamentalists do indeed form different exchange rate expectations; chartists' expectations are more in line with trends while fundamentalists consider mean reversion slightly more.…”
Section: Discussionsupporting
confidence: 75%
“…In a somewhat forward-looking modification of this rule, it is often assumed that the influence of fundamentalism increases when the exchange rate deviates more clearly from its fundamental equilibrium (e.g., Bauer, De Grauwe, and Reitz, 2009). In line with recent empirical exchange rate modeling, De Grauwe and Grimaldi (2006) introduce transaction costs to incorporate a non-linear response of exchange rates to changes in fundamentals (e.g.…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…macro-finance-interaction) model framework because 1 A litereture overview can be found in Samanidou et al (2007), an empirical model contest in Franke and Westerhoff (2012a). For illustrative examples on exchange rate modeling consult Grauwe and Grimaldi (2005) and Bauer et al (2009). 2 A new literature designs agent-based macroeconomic models as object oriented simulations without the need for any equation system.…”
mentioning
confidence: 99%
“…It will be shown that the resulting market model is a natural generalization of the widely used geometric Brownian motion. Furthermore, it is shown that feedback-based trading strategies are able to skew prices (which is in line with [7]) and even cause bubbles. It will be discused how technical trading restrictions must look like in order to prevent bubbles.…”
Section: Motivation and Introductionmentioning
confidence: 65%